Community perceptions of the Sumatran Tiger (Panthera tigris sumatrae) in Besitang District, Langkat Regency: Case study of Bukit Mas Village - Pindi Patana; Wanda Afnes Rahmatika (Global Forest Journal, 2024)
Sumatran tigers (Panthera tigris sumatrae) currently face various threats, such as deteriorating habitat quality and quantity due to forest conversion, exploitation, forest encroachment, and increased poaching. Bukit Mas Village, Besitang District, Langkat Regency is one of the villages that are quite close to the Gunung Leuser National Park (GLNP) area. This study aims to analyze community perceptions of human and Sumatran tiger conflicts (HTC). This study used a descriptive quantitative method. The respondents were taken using a non-probability sampling technique. Criteria were designed with purposive sampling type. The results of the study explain that the existence of conflict can affect people's perceptions of the existence of Sumatran tigers. The community considers tigers to be not beneficial to people's lives because tigers disturb public order. Age and latest education do not correlate (relationship) with community perceptions. Due to the Asymp. Sig values of 0.772 and 0.625. This value is greater than the significance level of 0.05